The Mother Character's Use of Directive Illocutionary Acts in 'The Croods: A New Age' Movie - Ketut Dika Widhyayukti; Putu Nur Ayomi (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2024)
Abstract The study aims to identify and analyze the categories of directive illocutionary acts performed by Ugga, the mother character in The Croods: A New Age movie using Searle's (1979) theory, supported by Halliday and Hasan's (1989) theory of the context of the situation. Employing observation and note-taking methods for data collection, this study utilizes a descriptive qualitative approach for analysis. The results revealed five categories of directive illocutionary acts: Ordering (14 utterances, 41.18%), directing (2 utterances, 5.88%), warning (2 utterances, 5.88%), asking (11 utterances, 32.35%), and suggesting (5 utterances, 14.71%). The study found ordering to be the most dominant illocutionary act category, indicating that characters often exert authority or urgency in their interactions toward other characters. Keywords: Directive, Illocutionary Act, Movie Abstrak Studi ini bertujuan untuk mengidentifikasi dan menganalisis kategori tindakan ilokusi direktif yang dilakukan oleh Ugga, tokoh ibu dalam film The Croods: A New Age dengan menggunakan teori Searle (1979), didukung oleh teori Halliday dan Hasan (1989) mengenai konteks situasi. Dengan menggunakan metode observasi dan pencatatan untuk pengumpulan data, studi ini menerapkan pendekatan kualitatif deskriptif untuk analisis. Hasil studi mengungkapkan lima kategori tindakan ilokusi direktif: Perintah (14 dialog, 41,18%), pengarahan (2 dialog, 5,88%), peringatan (2 dialog, 5,88%), pertanyaan (11 dialog, 32,35%), dan saran (5 dialog, 14,71%). Studi ini menemukan bahwa perintah adalah kategori tindakan ilokusi yang paling dominan, menunjukkan bahwa karakter sering kali menunjukkan otoritas atau urgensi dalam interaksi mereka terhadap karakter lain. Kata kunci: Direktif, Tindakan Ilokusi, Film